Salt‐Mediated Polyampholyte Hydrogels with High Mechanical Strength, Excellent Self‐Healing Property, and Satisfactory Electrical Conductivity. (16th September 2018) - Long, Tangjie; Li, Yixuan; Fang, Xu; Sun, Junqi
Abstract: In this work, self‐healing polyampholyte hydrogels with high mechanical strength in megapascal order, good resilience, improved toughness, and satisfactory conductivity are fabricated via one‐step polymerization of positively charged imidazolium‐based ionic liquid monomers containing urea groups and negatively charged 3‐sulfopropyl methacrylate potassium salt monomers followed by subsequent dialysis in water. Dialysis can remove partial counter ions in the original hydrogels to strengthen electrostatic interactions between imidazolium and sulfonate groups and improve mechanical strength of the hydrogels. After dialysis for 3 d, the originally soft hydrogels become mechanically robust with a tensile strength of ≈1.3 MPa, strain at break of ≈720%, and toughness of ≈6.7 MJ m −3 . Hydrogen‐bonding interactions between urea groups, which act as sacrificial bonds to dissipate energy, are important to improve the mechanical strength and toughness of the hydrogels. More importantly, the hydrogel can automatically heal from physical cut at room temperature with a healing efficiency of ≈91% because of the reversibility of the electrostatic and hydrogen‐bonding interactions. Because of the undialyzed salts in the hydrogels, the mechanically robust hydrogels possess a satisfactory ionic conductivity of ≈3 S m −1 at room temperature and can serve as highly flexible and stretchable conductors with self‐healing capacity. Abstract : Self‐healing polyampholyte hydrogels with high mechanical strength, good resilience, improved toughness, and satisfactory conductivity are fabricated via copolymerization of imidazolium‐based ionic liquid monomers and sulfonate‐containing methacrylate monomers, followed by dialysis in water to partially remove salts. The hydrogels, which are cross linked by reversible electrostatic and hydrogen‐bonding interactions, can automatically heal from physical cut at room temperature to restore mechanical strength and conductivity.